Предмет: Алгебра, автор: polakovaanastasia133

ПОМОГИТЕ ПОЖАЛУЙСТА​

Приложения:

Ответы

Автор ответа: Miа16
0

Ответ:

1) \left \{ {{\frac{k+m}{9} -\frac{k-m}{3}=2 } \atop {\frac{2k-m}{6}-\frac{3k+2m}{3}  =-20}} \right. =\left \{ {{k=-9+2m} \atop {\frac{2k-m}{6}-\frac{3k+2m}{3} =-20 }} \right. =\frac{2(-9+2m)-m}{6} -\frac{3(-9+2m)+2m}{3} =-20

m=12

k=-9+2*12

k=15

Проверка:

\left \{ {{\frac{15+12}{9} -\frac{15-12}{3} =2} \atop {\frac{2*15-12}{6} -\frac{3*15+2*12}{3} =-20}} \right. =\left \{ {{2=2} \atop {-20=-20}} \right.

( k, m ) = ( 15, 12 )

Похожие вопросы
Предмет: Литература, автор: вольфа2007